COVID-19 in the nervous system: physiopathology and neurological manifestations - Valder Cavalcante Maia Mendonça Filho; Amanda Gomes de Oliveira; Isabelle de Fátima Vieira Camelo Maia; Ananda Carolina Moraes de Falcone; Beatriz Gioppo Betini; Lucas Bruno Rezende; Fernando Henrique Magri Alves (Arquivos de Neuro-Psiquiatria)
Background Coronavirus disease 2019 (COVID-19) is a viral infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Although respiratory manifestations have received greater visibility during the pandemic caused by this virus, numerous neurological complaints related to coronavirus 2 infection have been documented in several countries. These records suggest that this pathogen presents neurotropism, and it can cause different neurological conditions of varying intensity.